Theoretical Insight Into Diamond Doping and Its Possible Effect on Diamond Tool Wear During Cutting of Steel - Hao, Li; Manzhos, Sergei; Zhang, Zhijun (Frontiers in Materials, 2021)
Natural diamond tools produce extremely severe chemical wear during cutting of steels. As reported in our previous work, Ga doping of diamond has effect on suppressing graphitization process. We investigate interstitial and substitutional dopants of different valence and different ionic radius (Ga, B, He) to achieve a deeper understanding of inhibiting graphitization. In this study, Ab initio calculations are adopted to explore the effects of three dopants that might affect the diamond wear. We consider mechanical effects via possible solution strengthening as well as electronic effects via dopant-induced modifications. We find that the bulk moduli difference between pristine and doped diamond is clearly related to strain energies. Furthermore, boron doping makes the resulting graphite more perfect results with stable sp2 hybridization, but Ga doped diamond needs 2.49eV to form the second graphene-like layer, which would result in the suppressed graphitization and the reduced chemical wear of diamond tool.